The times they are a-changing: Self-directed long-term services and supports and gerontological social work. Issue 2 (17th February 2019) - Sciegaj, Mark; Hooyman, Nancy R.; Mahoney, Kevin J.; DeLuca, Casey
ABSTRACT: The Partnerships for Person-Centered (PC) and Participant-Directed (PD) Long-Term Services and Supports (LTSS) Project (Partnerships Project) was a three-year effort funded by the New York Community Trust to develop and implement social work curriculum that would better prepare students for the changing practice demands of the aging and disability services network for self-directed LTSS (SD-LTSS). This article first describes the growth of SD-LTSS and the need for trained social workers on this service delivery model. The paper then describes the Partnerships Project that involved schools of social work along and aging and disability network organization partners in nine states. This description includes the major activities of the project including the creation of SD-LTSS competencies for social work education, the infusion of these competencies in beginning and advanced social work classes, and student assessment of their attainment of these competencies. This article then discusses the challenges to institutionalizing such curricular changes within social work programs and the need for a national strategy to train social workers for the demands of SD-LTSS.